Effect of supplementation with Saccharomyces cerevisiae on milk production and quality in cattle from Valle de Sibundoy, Putumayo, Colombia - Narváez Herrera, Juan Pablo (2021)
The aim of this study was to evaluate the effect of inclusion of two levels of Saccharomyces cerevisiae in the production and composition of bovine milk from the high tropics of the department of Putumayo, Colombia. Twelve Holstein cows were used at the beginning of lactation and of 450 kg of body weight, in a cross-over design. The cows were assigned to two treatments with two inclusion levels of S. cerevisiae (T1, 100 g and T2, 150 g) in the supplement. The study was conducted in two periods of 12 days (seven days of adaptation and five days of evaluation). The quality and production of milk were determined, as well as the indicators of the metabolic profile (glucose, cholesterol and blood urea nitrogen). No significant differences were found for milk production (14.86 vs 14.27 kg cow day) or in the metabolic profile, but there was a higher proportion of protein and fat in the milk of T1 cows (p <0.05).